Limpeza uterina após infusão de carvão e níveis de metabólitos plasmáticos de prostaglandina (PGFM) pós-infecção na égua - Nogueira, Carlos Eduardo Wayne (2001)
Persistent endometritis is a major cause of infertility in the mare. Two experiments were conducted aiming a better understanding of endometritis pathogenesis in the mare. In the first experiment uterine clearance after 250 e 500mg of charcoal infusion through uterine lavage 24 and 48hours thereafter was evaluated. Mares with major endometrial histological changes performed a delayed clearance of the charcoal infusion. It was observed that the 48 hours period was better than the 24 hours period to evaluated uterine clearance. The second experiment was designed to evaluate the plasma PGFM levels during the first 24 hours after an experimental infection with Streptococcus zooepidemicus. Twenty-two mares, previously used in the first experiment were infected. The mares were allocated in three groups: the control group consisted of the mares that cleared the infection whereas group 2 and 3 (Groups II and III of KENNEY, 1978 and SILVA et al., 1987) were composed of the mares that did not clear the infection after 96 hours. The control group showed more homogeneous PGFM plasma levels during the 24hours after the infection, with an average of 478pmol/L (210-668pmol/L). For Group 2, rising levels of PGFM were observed up to 4hours and then a fall until 9 hours and stable levels up to 24 hours after infection (X=273pmol/L; 112-706pmol/L). In Group 3, all mares had an average level of PGFM 1700pmol/L in the first blood sample. Those high levels were stable during the first three hours, following by a progressive fall up to the 16th hour, when they began to rise (X=283pmol/L; 102-1689pmol/L). Although the average PGFM levels were different among three groups, the difference was not statistically significant. This could be explained by the marked variations of individual values, independently of the groups considered. The relationship between uterine clearance and prostaglandin secretion in the healthy mare could be ascribed to the intensity and frequency of uterine prostaglandin secretion which is related to endometrial integrity. These results although do not point to any tight correlation between uterine charcoal clearance and plasmatic levels of PGFM may suggest that a regular/homogenous and constant pattern of prostaglandin secretion is more important than secretion intensity.